Randomized comparison of liposomal amphotericin B versus placebo to prevent invasive mycoses in acute lymphoblastic leukaemia - Cornely, Oliver Andreas; Heußel, Claus Peter (The journal of antimicrobial chemotherapy, 2017)
Abstract. Objectives: To prevent invasive fungal disease (IFD) in adult patients undergoing remission-induction chemotherapy for newly diagnosed acute lymphobl